Modalidades discursivas de la producción de textos críticos y de difusión en publicaciones argentinas online: cine, teatro y artes visuales - Proyecto - Dámaso Martínez, Carlos (2015)
In the first period of our research we plan to gather and analyze the distinctive features that can be found in criticism and diffusion of the different arts selected (cinema, theater and visual arts) on current online formats. As a starting point we will have some hypotheses which we will evaluate by reviewing multiple online sites to establish modalities and distinctions in written criticism. Although there are many studies about online publications, we have observed that only a few are centered on the aspects and modalities of writing in the art criticism. In this respect, we think that our research could be a significant contribution.